Evaluation of Antioxidant and Anticancer Activity of Kohautia Aspera (Heyne Ex Roth) Bremek - Kavitha G; Sivakkumar T; Elessy Abraham (Journal of Global Pharma Technology, 2020)
The purpose of present study was to investigate the antioxidant and anticancer activities of selected extracts of Kohautia aspera (Heyne ex Roth) Bremek. The chloroform, water and ethanolic extracts which are rich in phytoconstituents were subjected to DPPH photometric assay and standard MTT assay. The percentage of growth inhibition in antioxidant study increased with increasing concentration of extracts. The ethanolic extract showed better antioxidant activity followed by other extracts. The anticancer potential of plant was investigated by standard MTT assay against SK-MEL 28 skin cancer cells. In vitro cytotoxic activity of plant increased with increasing concentration of extracts. The results clearly indicated that the extracts of the study species has potential inhibition of free radicals and powerful anticancer activity against skin cancer cells.